2009
DOI: 10.1002/jrs.2414
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of conducting poly (methyl methacrylate)/polyaniline dodecylbenzenesulfonate blends

Abstract: Polyaniline soluble in organic solvents was prepared using dodecylbenzenesulphonic acid (DBSA) as functional dopant. The solubility parameter was calculated and the most suitable solvent chloroform was checked for the solubility and the most compatible polymer PMMA was selected for blending. Miscibility was maximized with 1% by weight of hydroquinone. Blending of doped polyaniline with dodecylbenzenesulphonic acid (PAni.DBSA) in poly (methyl methacrylate) (PMMA) was explained by a change in the conformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…PAni-B spectra presented characteristic bands at 1170 (C-H bending); 1206 (C-N stretching); 1502 (C=N stretching); 1560 (N-H bending) and 1598 cm −1 (C=C stretching) (Mažeikienė et al 2007;Cirić-Marjanović et al 2008;Moravková et al 2012). PAni-DBSA spectra, in turn, presented characteristic bands at 1190 (C-H bending); 1,260 (C-N stretching); 1,343 (C-N + stretching); 1,530 (C-C stretching); and 1620 cm −1 (C-H stretching) (Nobrega et al 2012;Ibrahim 2013;Shakoor and Rizvi 2010). The conductive nature of PAni-DBSA can be associated to the band located at 890 cm −1 (arrow in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 98%
“…PAni-B spectra presented characteristic bands at 1170 (C-H bending); 1206 (C-N stretching); 1502 (C=N stretching); 1560 (N-H bending) and 1598 cm −1 (C=C stretching) (Mažeikienė et al 2007;Cirić-Marjanović et al 2008;Moravková et al 2012). PAni-DBSA spectra, in turn, presented characteristic bands at 1190 (C-H bending); 1,260 (C-N stretching); 1,343 (C-N + stretching); 1,530 (C-C stretching); and 1620 cm −1 (C-H stretching) (Nobrega et al 2012;Ibrahim 2013;Shakoor and Rizvi 2010). The conductive nature of PAni-DBSA can be associated to the band located at 890 cm −1 (arrow in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 98%
“…They found that Raman intensities computed for chains of different lengths allow one to conclude that cumulenic molecules could be detected and identified. Solutions of polyaniline in organic solvents were prepared by Shakoor and Rizvi using dodecylbenzenesulfonic acid as a functional dopant . They then used Raman spectroscopy to characterize the blending process of two polymers with the aim of understanding the transformations in different types of charged segments.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…Single crystals CdPS 3 were prepared by direct method by heating a mixture of stoichiometric amounts of elemental Cd, P and S powders in an evacuated quartz tube at 800 to 900°C for 10 days [26,27]. The resulting material contained mostly small crystals, but also included a few large, thin single crystals about 1 cm 2 in area and 5 to 20 mm in thickness.…”
Section: Synthesis Of Cdpsmentioning
confidence: 99%
“…Insertion of intrinsic conducting polymer in layered host materials results in a dramatic modification of the physical properties, which has led to various applications as nonlinear optical materials [14,15], magnetic materials [16,17], catalysts and cathode materials in battery applications [18,19]. Different synthetic approaches [20,21] combining a variety of host [22] and guest molecules [23][24][25] [26][27][28] and the literature on its counterpart using density functional theory based calculations is still lacking.…”
Section: Introductionmentioning
confidence: 99%